Detection Model With a Maximum Discounted Effort Reward Search to Maintenance a Best Decision Under the Quality Control Process (Statistics, Optimization & Information Computing, 2022)
This paper aims to get a needed service by making the best decision of choosing one suitable company (queue) from K − independent Markovian queues (companies). The customers arrive at each queue according to a Poisson process. The service time of each customer has an exponential distribution. In a steady-state, the best decision depends on the minimum cost of detecting the suitable company which provides the best service with high speed (maximum service rate). To minimize the detection cost and maximize the probability of detection, we consider the search effort bounded by a Gaussian distribution as a function with a discounted parameter. The effectiveness of this model appears in a simulation study and the comparison with other models.